Overview of Work Stress Among Nurses in Hospitals - Prima, Irenne Agil; Pramana, Yoga; Mita, Mita (ProNers, 2024)
Background: Work stress is a critical issue in nursing that can impact productivity, performance, and overall well-being. Understanding the levels and factors associated with work stress among nurses can help in developing effective management strategies.Objective: To describe the levels of work stress and their association with demographic and professional characteristics among nurses in a hospital in West Kalimantan.Methods: This quantitative, descriptive cross-sectional study was conducted from May 12 to 14, 2023, involving 85 nurses working in inpatient wards. Data were collected using a structured questionnaire and analyzed using descriptive statistics with SPSS software.Results: Most respondents (75.3%) experienced normal levels of work stress, while 23.5% reported mild stress, and 1.2% experienced moderate stress. The majority of respondents were female (76.5%), aged 26"“35 years (77.6%), had 1"“5 years of work experience (51.8%), and held a D3 nursing degree (82.4%). Nurses with shorter work experience and practical education demonstrated better stress management, while high workloads and longer tenures were associated with increased stress levels.Conclusion: The findings indicate that the majority of nurses experienced manageable work stress levels, attributed to effective coping strategies and adaptability. Institutions should implement targeted interventions, such as workload management and wellness programs, to support nurses' mental health and job satisfaction. Further research is recommended to explore additional factors influencing work stress in diverse nursing populations